Вплив діджиталізації на нагромадження соціального капіталу економіки - Галушка, Зоя Іванівна (Чернівецький національний університет, 2024)
The article substantiates the essence and peculiarities of social capital as an economic resource and identifies the positive and negative impact of digitalization on its formation and accumulation. A comparative analysis is conducted, revealing a change in approaches to substantiating the essence of social capital. The accumulation of social capital is considered in an economic context. This is a process of increasing the economic opportunities of various participants in economic relations by expanding mutual trust, shared perceptions, and adherence to norms and values. It is an important mechanism for effectively conducting economic activities, fostering trust, and ensuring long-term benefits in business. The study of the impact of digitalization on the formation of the economy's social capital is based on the study of the systemic interrelation of forms of social capital existence, spheres, methods, and mechanisms of its accumulation, and conditions of reproduction. It is noted that this process has resource, environmental, and performance characteristics. The impact of digitalization on relationships between people is revealed, the essence of which lies in building trust, interaction, and cooperation, contributing to achieving common goals. This concerns the spread of trust and interaction, shared values and norms, strengthening social networks and connections, the emergence of new forms of social capital. It is noted that digitalization, including digital technologies, internet platforms, social networks, and other digital tools, can promote communication, cooperation, and interaction among individuals and groups, the formation of communities, and the exchange of ideas, resources, and support. It is shown that digitization significantly affects the operational efficiency of organizations, creating new opportunities and challenges for management. Digital tools and data analysis systems allow managers to quickly access critical information and analytics, enabling them to make rapid, informed decisions, gain deeper understanding of their organization and markets. Digitalization contributes to increased management efficiency, providing opportunities for effective decision-making, communication, and coordination, as managers utilize new tools and skills. Such approaches include flexible, iterative management processes, where work teams operate in short development cycles and regularly interact with customers. Negative aspects of the impact of digitalization on social capital are identified: the loss of the human factor in business relations; a decrease in empathy, sympathy, and the ability for constructive communication; issues of confidentiality and data protection due to the increase in the collection and processing of personal data in the digital environment; the spread of misinformation and fake news; the digital divide between those who have access to digital technologies and the skills to use them and those who do not.
Impact of digitalization on the accumulation of social capital in the economy
Keywords: digitalization, social innovation, social capital, accumulation of social capital, social security, social boundaries